Nexus of Non-Controlling Interests on Capital Structure: Macroeconomic and External Party Integrity as Moderator - Arisyahidin Arisyahidin; Marhaendra Kusuma; Sanju Kumar Singh; Mariano Nunes (Institute of Research and Community Outreach - Petra Christian University, 2026)
This study investigates the effect of share ownership of non-controlling interests (NCI) on capital structure policy and investigates moderating effects of macroeconomic fundamentals and integrity of independent external parties. NCI negatively impacts capital structure, consistent with the trade-off theory in capital structure policy. Companies that already obtain funding from NCI tend to reduce debt financing, and vice versa. Macroeconomic fundamentals reinforce the trade-off between corporate funding sources, whether debt or equity, related to the cost of debt and the cost of equity. The quality of independent external parties strengthens the investment decision of fund providers, whether in equity securities or corporate debt securities, considering the most favorable investment returns.